Interaction of Neuromelanin with Xenobiotics and Consequences for Neurodegeneration; Promising Experimental Models - Andrea Capucciati; Fabio A. Zucca; Enrico Monzani; Luigi Zecca; Luigi Casella; Tim Hofer (MDPI AG, 2021)
Neuromelanin (NM) accumulates in catecholamine long-lived brain neurons that are lost in neurodegenerative diseases. NM is a complex substance made of melanic, peptide and lipid components. NM formation is a natural protective process since toxic endogenous metabolites are removed during its formation and as it binds excess metals and xenobiotics. However, disturbances of NM synthesis and function could be toxic. Here, we review recent knowledge on NM formation, toxic mechanisms involving NM, go over NM binding substances and suggest experimental models that can help identifying xenobiotic modulators of NM formation or function. Given the high likelihood of a central NM role in age-related human neurodegenerative diseases such as Parkinson's and Alzheimer's, resembling such diseases using animal models that do not form NM to a high degree, e.g., mice or rats, may not be optimal. Rather, use of animal models (i.e., sheep and goats) that better resemble human brain aging in terms of NM formation, as well as using human NM forming stem cellbased in vitro (e.g., mid-brain organoids) models can be more suitable. Toxicants could also be identified during chemical synthesis of NM in the test tube.